The Urgency Of Personal Data Protection For The Community: There Is Need For An Independent Commission - Karno Sabowo, Hudi; Hartati, Sri; Karyono, Hadi (International Journal of Educational Research & Social Sciences, 2022)
The presence of data innovation in the current era of globalization has progressed rapidly. This development can be seen from the proliferation of electronic commerce (e-commerce) in the trade, government, health, education, and mobile internet sectors. Personal Data is certain individual data that must be treated, then stored and kept true for all important data and must be kept confidential. Also, everyone has the option of obtaining legal guarantees against protection and mediation relating to individual matters. The development of information technology indirectly changes the mindset, including territorial boundaries, time, logic of thinking, work patterns, to manual behavior towards digital demands. The era of digitalization so far has not been able to provide definite legal protection. This is indicated by the rise of leaks because they have reaped logical consequences in the form of technologybased crimes because the existence of a computerized or digitized system has not been able to be prevented properly. This article uses normative juridical research methods, namely library research related to applicable laws and regulations, legal principles and relevant library sources. Everyone has the right to guarantee the protection of personal data. The ratification of the Personal Data Protection Bill into a law and the establishment of an independent institution must be carried out immediately so that the public feels more secure about their right to privacy. In addition, the lawsuit mechanism against the acquisition of personal data without the consent of the relevant parties can be made clearer along with the compensationprocess.